Aplikasi Pencetakan Dokumen Berbasis Web [Dukcapil Assistant] untuk Pelayanan Administrasi Kependudukan: (Studi Kasus: Dinas Kependudukan dan Pencatatan Sipil Kabupaten Nabire) - Gerry Novand Kaunang; Gunawan Prayitno; Kristia Yuliawan; Christian Paul Raymond (Jurnal Teknologi dan Informatika, 2023)
The efficiency of public services at the Population and Civil Registration Agency of Nabire Regency is faced with obstacles such as less than optimal service of citizenship administrative requirements documents that affect the smoothness of citizenship administration. The printing of citizenship administrative requirements documents such as forms and letters is still done manually and requires additional time which greatly affects the duration of service with a fairly large population level. Conventional concepts that are commonly applied, such as creating documents using Microsoft Word, do not balance time consistency and people's patience and satisfaction in waiting for the administration process per person. The purpose of this research is to utilize existing computer technology resources, where the document service needs are implemented into an application so that the speed of access and printing of documents will be more efficient. The design of web-based applications here uses the Waterfall type SDLC (Software Development Life Cycle) method. The results of this study are a web-based application that is easy to operate and quickly delivers results, as a technological facility that can assist in citizenship administration service activities that were previously done manually, to be faster. To test the feasibility of the application runs well, a testing phase is held using Black Box Testing with the test results showing that each application feature can run properly according to its function so that the system is considered good and ready to use.